Oxidative Stress Markers in Urine and Serum of Patients with Bladder Cancer - Sabina Galiniak; Mateusz Mołoń; Marek Biesiadecki; Agnieszka Mokrzyńska; Krzysztof Balawender (MDPI AG, 2023)
Oxidative stress is defined as an imbalanced state of the production of reactive oxygen species and antioxidant capacity that causes oxidative damage to biomolecules, leading to cell injury and finally death. Oxidative stress mediates the development and progression of several cancer diseases, including bladder cancer. The aim of our study was to determine markers of levels of the oxidative stress in serum and urine in the same patients in parallel in serum and urine. Furthermore, we tried to estimate the associations between oxidative stress markers and the type of cancer, its clinical stage and grade, as the well as correlations between serum and urinary markers in patients with bladder cancer. Sixty-one bladder cancer and 50 healthy volunteers as a control group were included. We determined the serum and urine levels of advanced oxidation protein products (AOPP), Amadori products, total antioxidant capacity, total oxidant status (TOS), oxidative status index (OSI), and malondialdehyde. We confirm that almost all markers are elevated in serum and urine from patients with bladder cancer than from healthy subjects. Moreover, we did not find differences in the level of oxidative stress markers and the type of tumor, its clinical stage, and grade. We noted correlations between serum and urinary biomarkers, in particular TOS and OSI. Our results clearly indicate the participation of oxidative stress in the development of bladder cancer.